The origins of indigenism : human rights and the politics of identity - Niezen, Ronald (University of California Press, 2003)
Ronald Niezen examines the ways the recent emergence of an internationally recognized identity - 'indigenous peoples' - intersects with another recent international movement - the development of universal human rights laws and principles. This movement makes use of human rights instruments and the international organizations of states to resist the political, cultural, and economic incursions of individual states.